Web-Based Sales System Development Using CodeIgniter Framework: A Case Study at Andesta Indah Store, Serang Regency - Putra, Arfiansyah; Aryono, Gagah Dwiki Putra; Mansyuri, Umar (JINAV: Journal of Information and Visualization, 2025)
The rapid advancement of information and communication technology has significantly transformed business practices, particularly through the emergence of Electronic Commerce (E-Commerce). This study aims to design and develop a web-based sales application for Toko Andesta Indah, a micro, small, and medium-sized enterprise (MSME) located in Serang Regency, to address inefficiencies in manual sales processes and expand digital market reach. The system was developed using the Waterfall model and implemented with the CodeIgniter framework due to its lightweight structure and support for MVC architecture. The application features include user registration and login, product catalog display, order processing, payment proof upload, and administrative control of product and transaction management. Functional testing using Black Box methods confirmed that the system operates according to user requirements and supports secure, accurate, and efficient transactions. The results demonstrate that the developed system effectively simplifies transaction processes, enhances customer access to products, and provides administrative efficiency in managing sales data. This web-based application serves as a strategic step toward digital transformation for MSMEs and contributes to improving competitiveness in the e-commerce landscape.